Denervation versus pre‐ and postsynaptic muscle immobilization: Effects On acetylcholine‐ and muscle‐specific tyrosine kinase receptors. Issue 1 (23rd September 2016) - Kramer, Christopher; Zoubaa, Saida; Kretschmer, Alexander; Jordan, Denis; Blobner, Manfred; Fink, Heidrun
ABSTRACT: Introduction: Functional immobility of the diaphragm by mechanical ventilation impairs neuromuscular transmission and may result in ventilator‐induced diaphragmatic dysfunction. We compared 3 diaphragmatic immobilization models with respect to their effects on expression of adult and fetal acetylcholine receptors (AChRs), muscle‐specific receptor tyrosine kinase (MuSK), and muscle fiber morphology. Methods: Diaphragms of rats were immobilized by either: (1) phrenicotomy; (2) presynaptic tetrodotoxin nerve blockade; or (3) postsynaptic polyethylene orthosis. AChR subtypes and MuSK were quantified by Western blot and immunohistochemistry. Muscle fiber morphology was evaluated by hematoxylin–eosin staining. Results: Adult AChRs remained unchanged, whereas fetal AChRs and MuSK were upregulated in all models. Denervation induced the strongest changes in muscle morphology. Conclusions: Each diaphragm immobilization model led to severe morphologic and postsynaptic receptor changes. Postsynaptic polyethylene orthosis, a new model with an intact and functioning motor unit, best reflects the clinical picture of a functionally immobilized diaphragm. Muscle Nerve 55 : 101–108, 2017